“We Are All Trying to Find a Way to Help Ourselves”: A Look at Self-Help Strategies Among Psychotherapy Clients - Chang, Sherilyn; Sambasivam, Rajeswari; Seow, Esmond; Tan, Geoffrey Chern-Yee; Lu, Sharon Huixian; Assudani, Hanita; Chong, Siow Ann; Subramaniam, Mythily; Vaingankar, Janhavi Ajit (Frontiers in Psychology, 2021)
Objective: This study examined self-help strategies engaged by psychotherapy clients and explored their views on such self-help approach. Methods: Secondary analysis of data from a qualitative research study was conducted. A total of 15 psychotherapy clients were recruited and data was collected via semi-structured interviews. Thematic analysis of data was conducted using inductive approach to examine the data. Results: Three main themes revolving self-help strategies were identified: (1) Types of self-help strategies, (2) Reasons for engaging in self-help activities, and (3) Effectiveness of self-help strategies. Conclusions: The self-help approach to manage distress is common among psychotherapy clients. This study provided insights into understanding how and why clients use self-help strategies in their daily lives.